2020
DOI: 10.14203/treubia.v47i2.4005
|View full text |Cite
|
Sign up to set email alerts
|

First Report on Hunting Behavior of Migratory Oriental Honey-Buzzard (Pernis Ptilorhynchus Orientalis) Towards Migratory Giant Honeybee (Apis Dorsata Dorsata) (Hymenoptera: Apidae) on Java Island, Indonesia

Abstract: Both Migratory Oriental Honey-buzzard (Pernis ptilorhynchus orientalis) and migratory giant honeybee (Apis dorsata dorsata) can be found in South-east Asia. The Oriental Honey-buzzard is the main predator of the giant honeybee, prey upon its honeycomb, larvae, and honey. Its existence always follows the migration of the giant honeybee. They stay on Java island during the migratory season. The giant honeybee lives in a large colony and has a powerful sting that is useful for defence against its predators. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The predators can distinguish the bee comb to contain young stages (larvae and pupae), honey, bee pollen, and wax. The comb is a nutritious foraging target of animal predators including protected endemic animals of honey bear (Heliarctos malayanus), orangutan (Pongo pygmaeus), and other animals [56].…”
Section: The Benefit Of Stingless Beementioning
confidence: 99%
“…The predators can distinguish the bee comb to contain young stages (larvae and pupae), honey, bee pollen, and wax. The comb is a nutritious foraging target of animal predators including protected endemic animals of honey bear (Heliarctos malayanus), orangutan (Pongo pygmaeus), and other animals [56].…”
Section: The Benefit Of Stingless Beementioning
confidence: 99%
“…Sarang tersebut merupakan sarang persinggahan untuk mencari wilayah baru atau habitat baru untuk persarangan tahunan, walaupun posisi sarang berada di dekat perkebunan masyarakat. Kahono et al (1999) mengatakan bahwa sarang A. dorsata terletak pada ketinggian dibawah 10 m dari permukaan tanah selama jangka waktu dua tahun. Pada desa sampel ditemukan sisiran sarang A. dorsata juga terdapat di tempat terbuka, menggantung pada tebing batu dan dahan pohon-pohon yang besar seperti pohon salawaku dan pohon beringin setinggi lebih dari 10 m diatas permukaan tanah, letak sisiran sarang Apis dorsata berdekatan antara satu dengan alinnya, pada 1 pohon dapat ditemukan puluhan koloni.…”
Section: Sebaran Berdasarkan Ketinggian Tempat (Alitude) Dan Ketinggi...unclassified
“…The nests of A. dorsata usually hang on the branches of large trees and cluster on one tree with the number reaching tens to hundreds of nests (Kahono et al, 1999;Hadisoesilo 2001;Hepburn and Radloff 2011;Mead 2013). In general, A. dorsata tends to like the habitus of tall trees with relatively open branches and not too dense canopy as nesting sites (Starr et al, 1987;Mokosuli, et al, 2013), although it has been found that there is only one colony in one area.…”
Section: Indonesian Biodivers Jmentioning
confidence: 99%